Notifiche
Cancella tutti

Integrale

  

1
243

Spiegare il ragionamento, argomentare.

Autore
1 Risposta



2

Estremamente semplice. Scocciante solo da scrivere

 

a)

C(t) = S - Co k e^(-kt) dt = Co e^(-kt) + C'

e poiché C(0) = Co

Co = Co *1 + C' => C' = 0

e allora C(t) = Co e^(-kt)

 

Dopo 30 minuti ( 1/2 ora )

Cf = Co e^(-k/2)

DC = Cf - Co = Co e^(-k/2) - Co = Co ( e^(-k/2) - 1 )

 

b) Co e^(- 4 k) = 1/2 Co

e^(-4k) = 1/2

4k = ln 2

k = ln(2)/4

 

Infine

Co e^(-k T) = Co/10

e^(k T) = 10

e^(ln(2)/4 * T) = 10

2^(T/4) = 10

 

T = 4* log(10)/log(2) = 13.28 h ~ 13 h 17 min 16 s

 

 



Risposta
SOS Matematica

4.6
SCARICA